LEGAL LIABILITY OF LOCAL SELF-GOVERNMENT BODIES AND OFFICIALS FOR FAILURE TO IMPLEMENT PROGRAMS OF SOCIO-ECONOMIC DEVELOPMENT OF THE HROMADA - Tytykalo, Roman; Pavlovska, Nataliia; Kovalenko, Larisa (Baltic Journal of Economic Studies, 2022)
Local self-government is the leading institution of every developed, democratic society. Local self-government is an expression of the legitimate will of the population of a particular administrative and legal unit. That is why the exercise of powers and competence by local self-government bodies and officials is in fact an expression of the will of the population. In times of war, local governments are the closest to the needs of the population. This entity should respond comprehensively, as quickly and effectively as possible to the needs of its constituents. In order to develop the hromada, local self-government bodies are authorized to develop and adopt short-term and long-term (strategies) for the socio-economic development of the hromada. The level and quality of life of the population in a certain territory depends entirely on its successful implementation. The issue of the effectiveness of socio-economic programs of local self-government will be particularly acute in the postwar period, when it will be necessary to rebuild postwar Ukraine and its hromadas. The participation, professionalism, and responsibility of local government executive bodies and their officials will play a crucial role in this process. The authors emphasizes the need for more detailed legislative regulation of the issue of legal liability of executive bodies of local self-government and their officials. Given the above, it seems necessary to provide for the liability of executive bodies of local self-government and their officials for failure to implement programs of socio-economic development of a hromada.